Living with a reluctant hegemon explaining European responses to US unilateralism - Fehl, Caroline (Oxford : Oxford University Press, 2012)
The United States has achieved an unrivalled power position in the post-Cold War world, yet at the same time has been reluctant to accept new multilateral treaty commitments. This book sheds new light on the long-standing theoretical debate about the relationship between hegemony and international cooperation.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United States -- Foreign relations -- Europe; Europe -- Foreign relations -- United States; United States -- Foreign relations -- 2001-2009.; United States -- Foreign relations -- 2009-; Hegemony -- United States